Future Energy: Palembang Public Perception Of Briquettes As An Environmentally Friendly Energy Alternative - Zuhri, Aswan; Gunarto, Muji; Helmi, Sulaiman (International Journal of Marketing & Human Resource Research, 2025)
Non-renewable fossil fuels have raised global concerns due to their impact on the environment, including air pollution and climate change. As an alternative fuel, Briquettes offer an environmentally friendly solution by utilizing organic waste such as sawdust and coconut shells. This study explores Palembang residents' perception of briquettes as an alternative fuel, focusing on awareness, accessibility, price, and promotion. Interview findings indicate that although some residents know the benefits of briquettes, their adoption is hampered by uneven distribution, ineffective promotion, and less competitive prices. This study highlights the importance of technological innovation in improving the quality of briquettes as well as the role of the government in providing subsidies and education to the community. With the right strategy, briquettes have great potential to support the transition to more sustainable energy use